(untitled) (Jurnal Rimba Lestari, 2022)
Plants belonging to the genus Ficus have many benefits for the life of the people and animals in it for example as water system guard, absorbing CO2, feed sources and habitat for various species of animals and has potential as a traditional medicine. This research aims to identify the species and benefits of Ficus spp. at Sumber Agung DS Collection Block of Wan Abdul Rachman Tahura. Methods of collecting data carried out by surveying forest vegetation using the pathway method, interviews with forest land cultivators, and literature studies. Data were analyzed by identifying plant belonging to the genus Ficus using a guidebook and using descriptive analysis of the results of interviews with forest land cultivators. The results of this research showed that there are six species of plants of the genus Ficus, namely Ficus ampelas, Ficus septica, Ficus benjamina, Ficus variegata, Ficus hispida, and Ficus annulata which can be used as medicinal plants, animal and livestock feed, micro-climate providers, and ornamental plants. A further research is needed related to the suitability of the growing place for Ficus spp. and socialization by related agencies regarding the benefits and uses of plant members of the genus Ficus so that the community can further improve the maintenance and preservation of Ficus spp.